2020
DOI: 10.1186/s13072-019-0326-1
|View full text |Cite
|
Sign up to set email alerts
|

Recapitulation of gametic DNA methylation and its post-fertilization maintenance with reassembled DNA elements at the mouse Igf2/H19 locus

Abstract: Background: Paternal allele-specific DNA methylation of the H19 imprinting control region (ICR) regulates imprinted expression of the Igf2/H19 genes. The molecular mechanism by which differential methylation of the H19 ICR is established during gametogenesis and maintained after fertilization, however, is not fully understood. We previously showed that a 2.9-kb H19 ICR fragment in transgenic mice was differentially methylated only after fertilization, demonstrating that two separable events, gametic and post-f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 34 publications
1
10
0
Order By: Relevance
“…As mentioned earlier, we identified the 118-bp sequence that is essential for post-fertilization imprinted methylation of the mouse H19 ICR during the preimplantation period [17,18,27]. We further demonstrated that this sequence, together with the CTCF and Sox/Oct binding sequences, could confer imprinted methylation activity to the non-imprinted lambda DNA sequence both in transgenic [27] and endogenous genomic contexts [28].…”
Section: Introductionsupporting
confidence: 62%
See 1 more Smart Citation
“…As mentioned earlier, we identified the 118-bp sequence that is essential for post-fertilization imprinted methylation of the mouse H19 ICR during the preimplantation period [17,18,27]. We further demonstrated that this sequence, together with the CTCF and Sox/Oct binding sequences, could confer imprinted methylation activity to the non-imprinted lambda DNA sequence both in transgenic [27] and endogenous genomic contexts [28].…”
Section: Introductionsupporting
confidence: 62%
“…Since mIG-DMR analyzed at the same genomic location exhibited post-fertilization imprinted methylation, it is unlikely that the results in the rat sequence are related to the insertion site of the transgene. In addition, our previous reconstruction experiments showed differential methylation of the LCb118 fragment, in which the CTCF, Sox/Oct, and Zfp57 motifs were embedded in lambda DNA in the same context as the mouse H19 ICR and then combined with the mouse 118-bp sequence [28]. Because binding sequences for these factors are highly conserved in number and arrangement between mouse and rat H19 ICRs (Additional file 1: Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, following polyspermic fertilization, where methylation of the maternal genome remains relatively constant, up to five paternal genomes are demethylated in the zygote 4 . Although zygotic de novo DNAme of the maternal genome has been reported for the TKZ751 transgene and Igf2 59 , ETn retroelements 60 and H3K9me2-enriched regions 61 , to our knowledge, this is the first report to identify specific regions of the paternal genome subject to de novo DNAme by the 2C stage beyond the H19 gDMR 46 , 62 , 63 .…”
Section: Discussionmentioning
confidence: 76%
“…Two-fold rise for Igf2 gene (strongly linked to spermatogenesis, sex determination, testis development, infertility and prostate cancer; [Matsuzaki et al , 2020; Cannarella et al , 2020; Neirijnck et al , 2019; Damaschke et al , 2017]) has been also noticed. Igf2 and Klk proteins are enclosed in a common network consisted of proteins directly linked to fertility (Figure 6; Supplementary file 11; Supplementary file 12).…”
Section: Resultsmentioning
confidence: 99%
“…Our pathway analysis revealed a network including two genes with changed expression level in testis: Igf2 (2-fold increased) and Klk1b22 (8-fold decreased), supported by an interesting set of proteins linked to apoptosis and cellular processing (Figure 5; Figure 6; Supplementary file 11; Supplementary file 12). We can suggest that observed Igf2 overexpression in our study can be one of the associated factors leading to decreased sperm count and testis parameters in evaluated KO mice model because of its known relation to spermatogenesis and testis development [Matsuzaki et al , 2020; Cannarella et al , 2020; Neirijnck et al , 2019; Damaschke et al , 2017]. Documented reductions can be supported by the observed constrained expression of Klk1b22 – kallikrein mostly known from its neuronal activity; however, it cannot be excluded that we have revealed additional role of this protein, similar to the other members of the kallikrein family – role in semen liquefaction and degradation of extracellular matrix proteins in the interstitial area surrounding Leydig cells of the adult mouse testes ( Klk1b27 , Klk1b21 , Klk1b24 ) [Michaelis et al 2017; Marques et al , 2016, Du Plessis et al , 2013; Fink et al , 2007].…”
Section: Discussionmentioning
confidence: 99%